The effect of Kuntai capsule on ovarian function in cisplatin-induced premature ovarian insufficiency rats - Luo, Suiyu; Ruan, Xiangyan; Mueck, Alfred O. (Frontiers in Endocrinology, 2023)
Objective: This study aims to evaluate the effect of Kuntai capsule on ovarian function in cisplatin-induced premature ovarian insufficiency rats and to explore the mechanism of Kuntai capsule on the ovarian function of rats. Methods: Seventy-four female Sprague-Dawley rats were used for this study. Eight of the rats were randomly assigned to the Control group. The remaining sixty-six rats were utilized to establish the POI model via Cisplatin and then randomly divided into four groups: the model Control group, the Estradiol group, and groups treated with low and high doses of Kuntai capsule. For the 28-day administration, the Control and model Control groups were intragastrically administered with 2.0 mL of 0.9% sodium chloride daily, the Estradiol group with 2.0 mL of Estradiol suspension (0.2mg/kg/d), and the low dose Kuntai capsule group and the high dose Kuntai capsule group with 2.0 mL of Kuntai capsule suspension (0.6g/kg/d, 1.8g/kg/d, respectively). Sex hormone levels, estrous cycle, and ovarian coefficient of the five groups were compared, histological sections analyzed follicle counts, and the protein expressions of growth differentiation factor 9, light chain 3 A-II, and Beclin 1 in the ovarian tissue were detected by Western blotting. Results: After the 28-day administration, the serum Estradiol and Follicle-Stimulating Hormone levels of the group treated with low dose of Kuntai capsule were not significantly different from the Control group, the serum anti-Müllerian Hormone level of the group treated with high dose of Kuntai capsule was significantly higher than the Estradiol group. The estrous cycle of the group treated with low dose of Kuntai capsule was significantly lower than the model Control group. Regarding ovarian coefficient, resting and growing follicles, growth differentiation factor 9, light chain 3 A-II, and Beclin 1 expression, both Kuntai capsule groups outperformed the model Control group with the statistical difference (P<0.05). Conclusion: Kuntai capsule can improve the estrous cycle and ovarian coefficient of rats with premature ovarian insufficiency, maintain the number of resting and growing follicles, and up-regulate the protein expression of growth differentiation factor 9, light chain 3 A-II, and Beclin 1 of rats' ovaries.